Potentiometric Studies of Some Ternary System of Cu(II) Complexes with Picolinic Acid and Some Amino Acids - Durrani, Ayesha; Farooqui, Mazhar; Pakhare, Siddhartha; Nausheen, Siddiqui; Zaheer, Ahmed (Asian Journal of Chemistry, 2010)
The proton-ligand stability constants and stability constants of binary and ternary system of Cu(II) with picolinic acid, L-serine, tyrosine, threonine and phenylalanine have been studied potentiometrically at 25 ± 0.5ºC and μ = 1.0 M (NaClO4) in aqueous medium. The mixed ligand chelates are shown to have formed in simultaneous equilibria. Cu(II) forms 1 : 5 : 5 complexes with all chelating agents.